IMPROVING STUDENTS’ DESCRIPTIVE SPEAKING COMPETENCE BY USING CUE CARDS AT THE GRADE VIII 2 OF PUBLIC JUNIOR HIGH SCHOOL 03 BENGKULU CITY - Ruri Ariati (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2015)
This is a classroom action research that was carried out by implementing cue cards as the teaching media in class VIII 2 of Public Junior High School 03 Bengkulu city. This research was focused on whether the cue cards could improve students’ descriptive speaking competence and to determine the factors involved. This research was implemented to 36 students (19 female and 17 male) registered in this class. The progress was measured by several tests and some supporting data such as observation checklist, field note, and interview. The result of the research indicates that the improvement of subjects who were able to pass the target score (score ≥ 60) from 0% of students in pre test into 16% of students in post test in cycle 1 and finally becomes 36% of students in cycle 2. However, the factors those influence in improving students’ descriptive speaking competence are the students’ English proficiency, thinking ability of students, and students’ attitude and behavior along the treatment